Caracterización agro socio económica de los productores de chocho (Lupinus mutabilis) involucrados en el proyecto iniap fiasa, semillas andinas en las provincias de Chimborazo, Cotopaxi e Imbabura. 2022 – 2023. - Merizalde Suárez, Bryan Alejandro (2023)
The research was carried out in the Sierra Region, in the provinces of Chimborazo, Cotopaxi and Imbabura, specifically 38 lupine (Lupinus mutabilis) producers, who are associated with the Semillas Andinas project of the Agrobiodiversity Research Fund, Seeds and Sustainable Agriculture - FIASA in conjunction with INIAP, with the main objective of characterizing the agrosocioeconomic aspects of the producers with the use of social, economic and productive indicators, the Rural and Participatory Diagnosis Methodology (DRP) was used, which which allowed us to collect information with digital surveys according to the indicators to be studied, in order to cover the basic needs and problems of farmers, this survey was applied through the ODK-Collect application, the same one that gave us results in files spss for its subsequent coding in Excel, to be able to tabulate, code and graph the results, thus fulfilling the first objective of the investigation. We made a modification of the Sarandon (2006) methodology, the same one that was adapted to the characterization that was carried out, where the three social, economic and productive indicators could be coded, with values from 0 to 4, which allows calculating the averages. of each question by indicator, graphing them with amoebas or radials, in order to determine critical points, it will help us to better understand the situation of the 38 lupine producers, giving us results of three to four points per indicator, with averages of 0.00 to 1. ,16, giving us to understand that they are the weakest points of the research and in which more attention should be paid, for the same reason a linkage program with the community and the Technical University of Cotopaxi was recommended. ,